The Laser ablation of a metal foam: The role of electron-phonon coupling and electronic heat diffusivity - Rosandi, Yudi (2018)
The incidence of energetic laser pulses on a metal foam may lead to foam ablation. The processes occurring in the foam may differ strongly from those in a bulk metal: The absorption of laser light, energy transfer to the atomic system, heat conduction, and finally, the atomistic processes-such as melting or evaporation-may be different. In addition, novel phenomena take place, such as a reorganization of the ligament network in the foam. We study all these processes in an Au foam of average porosity 79% and an average ligament diameter of 2.5 nm, using molecular dynamics simulation. The coupling of the electronic system to the atomic system is modeled by using the electron-phonon coupling, g, and the electronic heat diffusivity, κe, as model parameters, since their actual values for foams are unknown. We show that the foam coarsens under laser irradiation. While κe governs the homogeneity of the processes, g mainly determines their time scale. The final porosity reached is independent of the value of g.